Tinjauan Perpektif Etik Naskah Srikandi Meguru Manah - Mardjono Mardjono (Institut Seni Indonesia Surakarta, 2008)
This article studies about wayang story Srikandi Meguru Manah from perspective etchic side. This activities of main characters, Srikandi and Arjuna are analyzed to know about the contained morality. From the analyses it can be found that Srikandi who leaves the palace without her parents’ permission is considered to be unworthy. Their behavior is considered to be against the palace value even thought it is meant to save palace. Arjuna is also considered to have less ethic for he places Srikandi in a pleasure garden (taman) when he teaches her technique of shooting by bow and arrow. As a married knight, Arjuna shouldn’t do that. On the other hand, their parents don’t accuse them and they even married them off.Keyword : ethic, story, wayang.